PELATIHAN MEMULAI USAHA UNTUK WIRAUSAHAWAN : CARA MERINTIS DAN MEMULAI BISNIS PADA KAUM MUDA - Zahra (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2026)
This community service activity seeks to improve business literacy and foster entrepreneurial motivation among young people in Tayando Langgiar Village, Tayando-TAM District, Tual City. The method employed was participatory training through outreach activities, discussions, and case studies, with an emphasis on understanding the basics of entrepreneurship, developing simple business plans, and providing information on access to financing and business networks. The activity results demonstrated a greater understanding of the basic principles of starting a business, an increased ability to develop a structured business plan, and increased motivation and courage to pursue independent entrepreneurship. This program also contributed to the creation of a network of young entrepreneurs with the potential to strengthen the local entrepreneurial ecosystem. Therefore, this activity is expected to be the first step in empowering young people and increasing their economic independence, as well as supporting the role of higher education in community development.